2022
DOI: 10.3390/life12071013
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dietary Saccharomyces cerevisiae on Growth Performance, Oxidative Status, and Immune Response of Sea Bream (Sparus aurata)

Abstract: The objective of this study was to evaluate the beneficial effect of Saccharomyces cerevisiae (SC) on growth, intestinal morphometric characteristics, blood indices, redox balance, expression of immune-related genes, and their involvement in disease resistance in sea bream (Sparus aurata). Three hundred healthy sea bream fingerlings were allocated into equal four groups (15 fish per hapa). The first group was served as a control and received a basal diet, while the other three groups were fed diets containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 79 publications
2
6
0
Order By: Relevance
“…Regarding liver function, liver enzymes (AST and ALT) are implicated in amino acid catabolism, and their higher activities in blood serum are considered a good indicator of liver damage. In this study, the higher levels of IMB coupled with the lower activities of liver enzymes confirmed that probiotic supplementation can improve the liver function of Nile tilapia, which was in general agreement with Fath‐El‐Bab et al (2022), who reported that the addition of B. coagulans in tilapia diet resulted in a significant decrease of liver enzymes activity.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Regarding liver function, liver enzymes (AST and ALT) are implicated in amino acid catabolism, and their higher activities in blood serum are considered a good indicator of liver damage. In this study, the higher levels of IMB coupled with the lower activities of liver enzymes confirmed that probiotic supplementation can improve the liver function of Nile tilapia, which was in general agreement with Fath‐El‐Bab et al (2022), who reported that the addition of B. coagulans in tilapia diet resulted in a significant decrease of liver enzymes activity.…”
Section: Discussionsupporting
confidence: 92%
“…It is well known that balanced diets have a dynamic effect on the body composition of fish (Fath‐El‐Bab et al, 2022). The production of digestive enzymes could be increased by the supplementation of IMB, which could promote the nutrient composition of aquatic animals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was thought to be caused by the additional nutrient contribution and the increase in digestibility in the fermented feed. The results obtained previously generally showed that the use of S. cerevisiae as a feed additive was positively correlated with the appearance of body weight of Sea Bream (Sparus aurata) [21].…”
Section: Discussionmentioning
confidence: 87%